2021
DOI: 10.1186/s40359-021-00700-9
|View full text |Cite
|
Sign up to set email alerts
|

The perception of the leader as an attachment figure: can it mediate the relationship between work engagement and general/citizenship performance?

Abstract: The study aimed to explore the perception of the leader as a security provider as a potential mediator of the relationship between work engagement and perceived general and citizenship work performance. Five hundred and forty-two adults completed the Leader as a security provider scale, Utrecht work engagement scale, General work performance questionnaire, and Citizenship organizational behavior questionnaire to self-report on their organizational behaviors. The perception of the leader as a secure attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Perceiving a specific leader as a security provider in followers did not contribute to their perceived task performance (at the level). Similarly, previous research denies the relationship between the constructs (Lisá et al, 2021). The possible interpretation has to do with the nature of the task performance.…”
Section: Team Performance and General Performancementioning
confidence: 97%
See 4 more Smart Citations
“…Perceiving a specific leader as a security provider in followers did not contribute to their perceived task performance (at the level). Similarly, previous research denies the relationship between the constructs (Lisá et al, 2021). The possible interpretation has to do with the nature of the task performance.…”
Section: Team Performance and General Performancementioning
confidence: 97%
“…Although the scale is believed to tap all functions of the attachment figure in leaders, it is unidimensional. However, later studies have shown two dimensions of the scale, "secure figure" and "separation distress" (Lisá et al, 2021;Mrázková & Lisá, 2022).…”
Section: Transformational Leader and Attachment Figurementioning
confidence: 99%
See 3 more Smart Citations